A Low Cost Vehicle Counting System Based On The Internet of Things - Lanny Sitanayah; Apriandy Angdresey; Jeri Wahyu Utama (EPI International Journal of Engineering, 2021)
In urban areas where land for parking is very limited, drivers often waste time, fuel, and emissions circling around without information if unoccupied parking spaces are available or not. In this paper, we design and implement a low-cost wireless system to count the number of cars and motorcycles in a parking lot. The system consists of two sensor devices, which are installed at an entrance gate and an exit gate of a parking lot. Each device has a NodeMCU ESP8266, an HC-SR04 ultrasonic sensor, and an MPU-9266 accelerometer. We use REST API as the web service to connect sensor devices and users, who will access the parking information using a web browser. The C4.5 algorithm is utilized to construct a decision tree to classify detected objects as cars, motorcycles, or people. We show by experiment that our sensor devices and the wireless monitoring system work correctly.